Eksplorasi Praktik Nilai-Nilai Kepemimpinan Asta Brata di Kabupaten Tabanan - Nigraha, Ni Made Ayu Basita Indria; Werang, Basilius; Trisna, Gusti Ayu Putu Sukma (DAS Institute, 2024)
This study aims to analyze the application of the Asta Brata leadership style among elementary school principals in Kediri District, Tabanan Regency. Rooted in Hindu ethical values, the Asta Brata leadership style emphasizes ideal leadership qualities symbolized by elements of nature, such as the sun, fire, sky, and earth. This research employs a qualitative approach with a phenomenological design to explore principals' experiences in applying these values. Data were collected through in-depth interviews and observations of several informants. The findings reveal five key themes in Asta Brata leadership: well-being, leadership spirit, role model, and courage. Principals who incorporate these values are able to create an inclusive, harmonious educational environment that motivates all school members. Based on these findings, it is recommended that Asta Brata-based leadership training be implemented to strengthen principals’ leadership quality, enhancing the performance and satisfaction of all educational stakeholders.